Understanding ethics - Preston, Noel (Federation Press, 2007)
Suitable for students taking courses in ethics and philosophy, this book explains the basics of ethical philosophy and applied moral reasoning to contemporary and perennial human dilemmas: truthtelling and honest; sex, love and morality; life, death and bioethics; public responsibility and political ethics; and, business and professional ethics.